Relação filogenética, virulência e resistência aos antimicrobianos de Salmonella spp isoladas de alimentos e pacientes clínicos: Interface entre segurança alimentar e saúde pública - Monteiro, Guilherme Paz (2020)
Salmonellosis is one of the most prevalent foodborne diseases in the world, with an impact on the economy and public health. Among the various serovars, we highlight S. Typhimirum for being one of the most involved in food-borne outbreaks and S. Heidelberg for being an emerging serovar associated with human outbreaks. The thesis was divided into three chapters. The first, general considerations, reports the general themes considered important for the reader's contextualization of what was discussed in the following chapters. The strains analyzed in chapters II and III were isolated from food and human patients in several states of Brazil, between 2011 and 2017, from the collection of Bacterial Enteropathogens cultures of the Oswaldo Cruz Institute (IOC / FIOCRUZ-RJ), which also provided the information about its origin. In the second chapter, 43 strains of S. Typhimurium were evaluated for the presence of virulence genes (sefA, invA, agfA, avrA, lpfA, sivH, hilA, spvC, sopE) and genes associated with antimicrobial resistance (qnrS and qnrA - fluoroquinolones; blaTEM and blaSHV - β-lactams) by the PCR technique. The minimum inhibitory concentration (MIC) determined the phenotypic resistance to the classes of antimicrobials considered important: meropenem: β lactam / carbapenem; colistin: polymyxins; ciprofloxacin: fluoroquinolones; ceftriaxone: β-lactams / 3rd generation cephalosporins. The PCR and CIM results were used to build virulence and resistance profiles. The dissemination and association of resistance and virulence profiles were discussed after genotyping using the Pulsed Field Gel Electrophoresis (PFGE) technique. In the third chapter, 36 strains of S. Heidelberg were analyzed, with objectives and methodology identical to those of chapter II, added by the sequencing of the complete genome of two phylogenetically distinct strains carried out by Illumina HiSeq 2500, in order to identify the virulent, resistance potential, treatment difficulties and public health risk.